A 3D nickel(II) coordination polymer constructed by mixed- ligand strategy: synthesis, crystal structure and sensing of Hg(II) ion. Issue 5 (11th April 2022) - Sun, Qiao-Zhen; Zhao, Bo; Chai, Li-Yuan; Liu, Hao; Jin, Hao-Zhe; Liu, Hui
Abstract: A new N-containing coordination polymer, namely, [Ni(L)(dpa)·2.5H2 O]n (1 ) (H2 L = 4, 4'-azanediyldibenzoic acid, dpa = 4, 4'-dipyridylamine) has been constructed under hydrothermal conditions. Structural analysis reveals that complex 1 exhibits a 3D 4-connected binodal net. With functional amino group, complex 1 is developed to detect heavy metal ions by colorimetric method. Notably, 1 can selectively detect Hg 2+ and it is free from the interference of other metal ions. The linear range for Hg 2+ detection is 0.1 to 0.5 mL. XPS shows that the N atoms of amino groups in 1 are responsible for the Hg 2+ detection. Graphical abstract: UF0001